Synthesis of azobenzenophanes with a large molecular cavity - Rajakumar, Perumal; Senthilkumar, B.; Srinivasan, Kannupal (Australian Journal of Chemistry, 2006)
The design and synthesis of four large-cavity azobenzenophanes, capable of forming photochemically controllable complexes with organic guest molecules, are described. These azobenzenophanes, possessing m-terphenyl, aromatic carbonyl, and chiral BINOL spacers, were synthesized from the corresponding bisphenols and dibromides using simple O-alkylation methodology. A preliminary photochemical study was carried out on the aromatic carbonyl spacer containing azobenzenophane, and the isosbestic points for the cis–trans isomerization process appeared at 319 and 419 nm.

One-pot process for the conversion of aroyl chlorides to acyl thioureas - Ramana, Chepuri V.; Senthilkumar, B. (WO2014087431A1, WO2014087431A8, 2013)
The present invention disclose an improved one pot process for synthesis of acyl thioureas of formula (I), with yield greater than 80%, from aroyl chlorides of formula (I) wherein, R′ is an aryl or a heteroarylene group substituted with one or more groups selected from hydrogen, alkyl, alkylene, alkynyl, alkoxy, alkenyloxy, halo, hydroxyl, nitro, amino, carboxyl, ester, halogenated hydrocarbon or an aryl or heteroaryl; R″ and R′″ are selected independently from hydrogen, alkyl, alkylene, alkynyl, alkoxy, alkenyloxy, halo, hydroxyl, nitro, amino or halogenated hydrocarbon.

Pd-catalyzed benzylic C-H oxidation of cyclotriveratrylene - product diversity - Senthilkumar, B.; Gonnade, Rajesh G.; Ramana, C. V. (Organic & Biomolecular Chemistry, 2015)
The inner-rim functionalization of CTV has been examined by employing Pd-catalyzed benzylic oxidation. The outcome of the oxidation depends upon the solvent and co-oxidants employed. An interesting array of CTV derivatives has been synthesized with a simple change in the conditions.

BQ-AurIPr: a redox-active anticancer Au(i) complex that induces immunogenic cell death - Mule, Ravindra D.; Kumar, Akhilesh; Sancheti, Shashank P.; Senthilkumar, B.; Kumar, Himanshu; Patil, Nitin T. (Chemical Science, 2022)
Immunogenic Cell Death (ICD) is a unique cell death mechanism that kills cancer cells while rejuvenating the anticancer immunosurveillance, thereby benefiting the clinical outcomes of various immuno-chemotherapeutic regimens. Herein, we report development of a library of benzo[a]quinolizinium-based Au(i) complexes through an intramolecular amino-auration reaction of pyridino-alkynes. We tested 40 candidates and successfully identified BQ-AurIPr as a novel redox-active Au(i) complex with potent anticancer properties. BQ-AurIPr efficiently triggered generation of DAMPs - the hallmarks of ICD - and was superior in terms of efficiency compared to FDA-approved drugs known to induce ICD. BQ-AurIPr significantly increased immunogenicity of cancer cells enhancing their phagocytosis when co-cultured with immune cells. Our investigation reveals that BQ-AurIPr induces oxidative stress inside mitochondria leading to mitophagy, as the mechanism for immunogenic cell death in A549 cells.